Comparison of the coagulopathies associated with COVID‐19 and sepsis. Issue 4 (18th May 2021) - Campbell, Robert A.; Hisada, Yohei; Denorme, Frederik; Grover, Steven P.; Bouck, Emma G.; Middleton, Elizabeth A.; Wolberg, Alisa S.; Rondina, Matthew T.; Mackman, Nigel
Abstract: Background: Coronavirus disease 2019 (COVID‐19) is associated with activation of coagulation that mainly presents as thrombosis. Sepsis is also associated with activation of coagulation that mainly presents as disseminated intravascular coagulation. Many studies have reported increased levels of plasma D ‐dimer in patients with COVID‐19 that is associated with severity, thrombosis, and mortality. Objectives: The aim of this study was to compare levels of circulating extracellular vesicle tissue factor (EVTF) activity and active plasminogen activator inhibitor 1 (PAI‐1) in plasma from patients with COVID‐19 or sepsis. Methods: We measured levels of D ‐dimer, EVTF activity, and active PAI‐1 in plasma samples from patients with COVID‐19 (intensive care unit [ICU], N = 15; and non‐ICU, N = 20) and patients with sepsis (N = 35). Results: Patients with COVID‐19 had significantly higher levels of D ‐dimer, EVTF activity, and active PAI‐1 compared with healthy controls. Patients with sepsis had significantly higher levels of D ‐dimer and EVTF activity compared with healthy controls. Levels of D ‐dimer were significantly lower in patients with COVID‐19 compared with patients with sepsis. Levels of EVTF activity were significantly higher in ICU patients with COVID‐19 compared with patients with sepsis. Levels of active PAI‐1 were significantly higher in patients with COVID‐19 compared with patients with sepsis. Conclusions: High levels of both EVTF activity and active PAI‐1 may promote thrombosis in patients with COVID‐19 due to simultaneous activation of coagulation and inhibition of fibrinolysis. The high levels of active PAI‐1 in patients with COVID‐19 may limit plasmin degradation of crosslinked fibrin and the release of D ‐dimer. This may explain the lower levels of D‐dimer in patients with COVID‐19 compared with patients with sepsis.